Video Animasi Sebagai Media Pembelajaran Efektif bagi Siswa Sekolah Dasar di Masa Pandemi COVID-19 - Zainal Abidin Achmad; Muhammad Iqbal Dwi Fanani; Ghifari Zaka Wali; Rizkiyatul Nadhifah (Universitas Mataram, 2021)
This article's background is the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the process of implementing school learning that has turned online. This article contains the process of making animated video learning media using the Powtoon application. Animated video material is the National Examination subject (Indonesian, Science, and Mathematics) for elementary school students in grades one to six. The data collection method used interviewing students, parents, teachers, village heads, PKK administrators, and youth organizations. By analyzing the problems then accomplished by making animated videos that suitable to the syllabus for each subject. The animated video is uploaded to the Sidokumpul Village Community Service Program's official Youtube channel to be accessed by all target elementary students and the wider community. Making animation is to provide learning innovation for elementary school teachers and students in Sidokumpul village and attract interest in learning. The stages of making animated videos consist of pre-production, production, and post-production. Animated videos can accelerate elementary students' understanding of the subject matter. Moreover, parental involvement in online learning provides many positive things for relationships between family members and student personality development.